Training on Website Application Development for Coffee Shop Visitors for Students - Akbar Iskandar; Kamaruddin; Erwin Gatot Amiruddin; Andi Jusriani (Jurnal Abdimas Cendekiawan Indonesia, 2024)
The world of education has changed, What world of education which used to be a transfer of knowledge with a standardized model is now changing more straightforwardly, students who used to only be able to learn through teachers/lecturers, schools, campuses, and literature books, are now facilitated by existing facilities, such as the internet, Study Clubs, and learning places that are more following the modern lifestyle of students. So the idea emerged regarding planning training activities in coffee shops/cafes which are recreational and educational facilities by paying attention to all the facilities needed as well as alternatives and new functions that are well adapted, comfortable, and not just for relaxing. Training activities to create a website in a coffee shop/cafe is an alternative to obtaining a comfortable, minimalist, and modern learning atmosphere. An atmosphere that makes anyone feel at home, not only just eating and drinking but also still processing their productivity. Doing activities in a coffee shop/cafe reflects the lifestyle of today's students, which is realized in a new learning method that is expected to represent the mindset, ideas, and creativity of students.